Competency Features of Forming Personnel Competence In The Conditions of Innovative Development - Amrullaevich, Saydiyev (Indonesian Journal Publisher, 2025)
This article analyzes scientific perspectives related to the examination of organizational employees' skill sets in modern socio-economic conditions. It focuses on personnel potential, work capacity, managerial ability, interpersonal communication skills, and individual characteristics in the professional activity process. The study also emphasizes the relevance of dialectical philosophical principles in understanding how human resources evolve under innovative pressures. In the context of innovative development, organizations must continuously adapt their human resource strategies by aligning with technological progress and societal expectations. The article considers both internal motivations and external influences on competence formation, such as technological advancement, environmental transformation, and the shift towards intellectual labor. Practical recommendations for developing employee competence are suggested based on existing scholarly theories and organizational practices.